2015
DOI: 10.1017/s146039691500028x
|View full text |Cite
|
Sign up to set email alerts
|

Deep Inspiration Breath Hold for left-sided breast cancer: experience from the patient’s perspective

Abstract: IntroductionThe dosimetric benefits of Deep Inspiration Breath Hold (DIBH) in reducing cardiac dose are well documented, however reports on the patient’s personal experience with this technique are limited. The purpose of this research is to investigate DIBH from the patient’s perspective and to provide recommendations to further improve the patient experience.Materials and methodsA questionnaire was used to record the patient’s comprehension of DIBH instructions and preparation for treatment. Levels of comfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The increased risk is proportional to the mean dose of radiation delivered to the heart. The addition of potentially cardiotoxic chemotherapy is a further complication to many of these patients and thus it is recommended that the radiation dose delivered to the heart be kept as low as reasonably possible . DIBH treatment has been developed to facilitate reduction in cardiac dose, by achieving the maximum separation between the treatment target area and heart, without compromise on the target volume coverage …”
Section: Introductionmentioning
confidence: 99%
“…The increased risk is proportional to the mean dose of radiation delivered to the heart. The addition of potentially cardiotoxic chemotherapy is a further complication to many of these patients and thus it is recommended that the radiation dose delivered to the heart be kept as low as reasonably possible . DIBH treatment has been developed to facilitate reduction in cardiac dose, by achieving the maximum separation between the treatment target area and heart, without compromise on the target volume coverage …”
Section: Introductionmentioning
confidence: 99%
“…All participants understood the technique, they could execute it well and felt satisfied afterwards. During the examinations we focused on creating a safe and repeatable environment with clear and simple instructions, since previous research has shown this improves the patient experience [18] , [39] . To create this environment, appropriate monitoring of the patients is required.…”
Section: Discussionmentioning
confidence: 99%
“…multi-beam intensity modulated radiotherapy (IMRT) for whole breast with lymph node irradiation, beam-on time can be extended to up to 5 min, especially in combination with hypofractionated schedules [15] , [16] . Therefore, a high number of consecutive short DIBHs are required, leading to stress for the patient, position changes and the inability of treatment in DIBH due to exhaustion for many patients [17] , [18] . Also, previous research has shown a moderate correlation between positional errors, mostly in the superior-inferior direction, and the number of DIBHs required, especially when treating the lymph node regions.…”
Section: Introductionmentioning
confidence: 99%